Pengaruh Gaya Kepemimpinan, Komunikasi, dan Budaya Organisasi Terhadap Kesejahteraan Karyawan - Siti Nur Isnaini; Wulan Purnamasari (widya balina, 2025)
Employee welfare is an important element in the success and sustainability of an organization. This study aims to analyze the influence of leadership style, communication, and organizational culture on employee welfare at PT Bintang Teknik Nyata Sukodono, Sidoarjo. Leadership style emphasizes the leader's ability to create a clear and strategic vision of the future to empower employees. Communication in an organization includes the effectiveness of information delivery, openness, and two-way communication between leaders and employees. Meanwhile, organizational culture includes shared values, behavioral norms, and adaptation to change that shape interaction patterns within the organization. This study uses a quantitative approach with a survey method, involving all employees of PT Bintang Teknik Nyata as respondents. Data were collected through a questionnaire designed to measure indicators of leadership style, communication, organizational culture, and employee welfare. The analysis was carried out using multiple linear regression to identify the partial and simultaneous effects of independent variables on employee welfareThis study is expected to provide theoretical and practical insights. Theoretically, the results of this study contribute to the development of human resource management science, especially related to leadership style, communication, and organizational culture. Practically, this study can be a reference for PT Bintang Teknik Nyata in formulating strategies to improve employee welfare through leadership optimization, communication improvement, and the formation of a supportive organizational culture.